The Association Accrual-Based Earnings Management on CEO and CFO Attribute: Thai Listed Companies - Meechana, Jitprapall; Petchchedchoo, Pattanant; Kumsuprom, Siridech; Panmanee, Panarat (Rajapark Journal, 2024)
This study examines the relationship between CEO and CFO attributes and Accrual-based Earnings Management (AEM) in Thai-listed companies on the SET100 index. It was conducted as quantitative research, analyzing data from 2020-2022 with a sample size of 75 companies. The study utilized multiple regression analysis and yielded the following findings: 1) CEO attributes such as age, work experience, relevant industry experience, stock ownership, and holding the position of chairman are correlated with AEM. 2) CFO attributes, including age, relevant work experience, stock ownership, and accounting certification, are also correlated with AEM.